A Vaccine Based on Kunitz-Type Molecule Confers Protection Against Fasciola hepatica Challenge by Inducing IFN-γ and Antibody Immune Responses Through IL-17A Production - Silvane, Leonardo; Celias, Daiana Pamela; Romagnoli, Pablo Alberto; Maletto, Belkys Angélica; Sanchez Vallecillo, María Fernanda; Chiapello, Laura Silvina; Palma, Santiago Daniel; Allemandi, Daniel Alberto; Sanabria, Rodrigo Eduardo Fabrizio; Pruzzo, César Iván; Motrán, Claudia Cristina; Cervi, Laura (Frontiers in Immunology, 2020)
Fasciola hepatica is worldwide distributed helminth parasite that causes fasciolosis, a chronic disease affecting mainly cattle, sheep, and occasionally humans. Triclabendazole is the drug of choice. However, the continuous use of this drug has led to the development of parasite resistance and consequently the limitation of its effectiveness. Hence vaccination appears as an attractive option to develop. In this work, we evaluated the potential of F. hepatica Kunitz-type molecule (FhKTM) as antigen formulated with a liquid crystal nanostructure formed by self-assembly of 6-O-ascorbyl palmitate ester (Coa-ASC16) and the synthetic oligodeoxynucleotide containing unmethylated cytosine-guanine motifs (CpG-ODN), during an experimental model of fasciolosis in mice and we further dissected the immune response associated with host protection. Our results showed that immunization of mice with FhKTM/CpG-ODN/Coa-ASC16 induces protection against F. hepatica challenge by preventing liver damage and improving of survival after F. hepatica infection. Besides, FhKTM/CpG-ODN/Coa-ASC16-immunized mice elicited a potent IFN- and IL-17A with high levels of antigen-specific IgG1, IgG2a and IgA serum antibodies. Strikingly, IL-17A blockade during infection decreased IgG2a and IgA antibody levels as well as IFN- production, leading to an increase in mortality of vaccinated mice. The present study highlights the potential of a new vaccine formulation to improve control and help eradication of F. hepatica infection, with potential applications for natural hosts such as cattle and sheep.